STRATEGI BERSAING PERUSAHAAN PELAYARAN DAN GALANGAN KAPAL SEBAGAI EFEK LESUNYA BISNIS BATU BARA DI INDONESIA - Rini Setiawati (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2017)
The purpose of this study is to analyze the strategies undertaken by some shipping companies and shipyard companies to survive and win the competition and through difficult conditions. The research method used is qualitative research with case study approach from some shipping and shipyard companies and with combination of SWOT method and Analytic Hierarchy Process (AHP) as decision making technique. The findings of the study suggest that all firms are defensive in to maintain their existence up today. AHP analysis shows significant factors to the development of shipyard business is Strength factor by 36.7% and Work Quality factor (20.8%) which is a very important factor compared to other factors. The priority of strategy making according to SWOT analysis is WT strategy (3.84 points) whereas according to AHP it is WO strategy (87.35 points) but both are strategies to minimize weakness.